2004
DOI: 10.1139/w04-074
|View full text |Cite
|
Sign up to set email alerts
|

Influence of substrate composition and flow rate on growth ofAzospirillum brasilenseCd in a co-culture with 3 sorghum rhizobacteria

Abstract: The ability of Azospirillum brasilense Cd to colonize the niche occupied by 3 bacterial strains previously isolated from sorghum rhizosphere was studied by means of the Biolog system. The isolates were identified by different methods as strains belonging to Pseudomonas putida, Stenotrophomonas maltophilia, and Klebsiella terrigena species. Several C sources, also chosen among the constituents of sorghum root exudates, were used to evaluate the metabolic profiles of Azospirillum and the sorghum rhizobacteria. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Data from Biolog appear as an indirect analysis, as it has been related to modifications in exudation patterns (Lippi et al . ; Alisi et al . ; García‐Villaraco Velasco et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Data from Biolog appear as an indirect analysis, as it has been related to modifications in exudation patterns (Lippi et al . ; Alisi et al . ; García‐Villaraco Velasco et al .…”
Section: Discussionmentioning
confidence: 99%
“…A better understanding of the relationships between microbial diversity and soil functions requires not only the use of more accurate assays for taxonomically and functionally characterizing DNA and RNA extracted from soil, but also high-resolution techniques with which to detect inactive and active microbial cells in the soil matrix (Nannipieri et al 2003). Data from Biolog appear as an indirect analysis, as it has been related to modifications in exudation patterns (Lippi et al 2004;Alisi et al 2005; Garc ıa-Villaraco Velasco et al 2009), and shifts in Biolog metabolic diversity patterns have been related to shifts in community composition (Schutter and Dick 2001;Crecchio et al 2004). Analysis of community-level catabolic profiling with RDA (Figs 4 and 5), indicated that sampling times and stress incidence were responsible of sample separation.…”
Section: Discussionmentioning
confidence: 99%